In-situ encapsulated catalyst and its application

By using CeO2 support for in situ encapsulation in methane chemical chain conversion, a highly dispersed metal nanoparticle catalyst is formed, which solves the problems of catalyst sintering and carbon deposits, and achieves efficient methane and carbon dioxide conversion.

CN116020456BActive Publication Date: 2025-02-07DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111239476.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-25
Publication Date
2025-02-07
Estimated Expiration
2041-10-25

AI Technical Summary

Technical Problem

Existing catalysts have problems of sintering, carbon deposits and low activity in methane chemical chain conversion, making it difficult to achieve efficient and clean conversion.

Method used

By using CeO2 support for in-situ encapsulation under a high-temperature reducing reaction atmosphere, a highly dispersed metal nanoparticle catalyst is formed to avoid sintering and carbon deposits, while improving catalytic activity.

Benefits of technology

The efficient dispersion and stability of the catalyst are achieved, sintering and carbon deposits are avoided, and the conversion of methane and carbon dioxide and the selectivity of synthesis gas are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116020456B_ABST
    Figure CN116020456B_ABST
Patent Text Reader

Abstract

The present invention relates to an in-situ encapsulated catalyst and its application. The catalyst is composed of metal nanoparticles and CeO2 carriers, the metal nanoparticles are prepared by a reduction method, and are one or two of Ni, Co, Ru, and Pt, the carrier CeO2 is prepared by a coprecipitation method, and the metal is loaded on the carrier by an impregnation method, and the metal loading is 0.05-5% of the catalyst mass to obtain a loaded catalyst. In the methane chemical chain reforming process, it shows very high stability and activity, and the methane, carbon dioxide conversion rate and synthesis gas selectivity are close to 100%. The present invention can also be used for solar thermal cracking water to produce hydrogen, because its in-situ generated high defect coating structure has excellent anti-carbon deposition ability, and the purity of hydrogen can reach 100%. In addition, the present invention can also be used for the catalytic decomposition of hydrazine propellants, ADN-based and HAN-based green propellants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic conversion of methane, carbon dioxide and water and the field of catalytic decomposition of hydrazines and green propellants, and in particular to an in-situ encapsulated catalyst and application thereof. Background Art

[0002] With the rise of the shale gas revolution and the exploitation of combustible ice, methane, as its main component, is an important energy and chemical raw material, and its output is increasing year by year. The clean and efficient use of methane has very important energy and environmental significance. However, at present, methane steam reforming and dry gas reforming are mainly used commercially to convert it into synthesis gas for the synthesis of high value-added products, but both processes are high-energy-consuming processes. The partial oxidation of methane to synthesis gas is an exothermic process with low energy consumption, but it has serious safety hazards when combined with oxygen in industry. Through the chemical chain conversion of methane, the reaction can be divided into two steps. The first step realizes the partial oxidation of methane and reduces energy consumption. The second step can realize the capture, cracking and water splitting of carbon dioxide to produce hydrogen, which solves environmental and energy problems and has a very broad application prospect. However, due to the excessive stability of methane, the catalyst activity is low, and the catalyst is easy to sinter and has poor stability, which makes it difficult to realize application. Therefore, improving activity, stability and anti-carbon deposition performance is of great significance to promote the clean conversion of methane, carbon dioxide and water.

[0003] Supported non-precious metal and precious metal catalysts are widely used in methane conversion, but they face serious sintering problems. A large number of studies believe that encapsulating active metals during preparation and hindering the migration of nanoparticles is an important measure to solve their sintering. There are mainly the following ways: one is to form a core-shell catalyst, which effectively avoids the aggregation of active metals during calcination and reaction. For example, NiCo alloy nanoparticles are encapsulated in SiO 2 The sphere (Nano Energy, 2018, 45, 101-108) effectively avoids the sintering of NiCo while improving the activity. Through the test of shell structures of different shapes, it is shown that the capsule structure can show good activity and metal anti-sintering performance under more stringent process conditions (Appl. Catal. B, 2019, 259, 118019). By regulating the composition of the shell, CeO with redox ability is introduced. 2 , forming Ni-SiO 2 @CeO 2 The structure can effectively inhibit coking and sintering (Appl. Catal. B, 2018, 230, 220-236, Fuel, 2021, 291, 120182). Secondly, the dispersion of nanoparticles can be achieved through mesoporous materials, which can regulate their catalytic properties and effectively alleviate the sintering process. For example, Fe 2 O3 The nanoparticles are confined in the pores of the SBA-15 molecular sieve (Nat. Commun., 2019, 10, 5503), which achieves the regulation of the activity of metal oxides while avoiding the sintering of metals, and has higher selectivity and stability. The third is to form an "armor" structure, which mainly uses two-dimensional materials to encapsulate metal nanoparticles and adjust the number of carbon layers to achieve the regulation of the activity of CoNi catalysts (Angew. Chem., Int. Ed., 2015, 54, 2100-2104), while ensuring the stability of the catalyst, and maximizing its activity. The above preparation method has a certain regulation on the activity and stability of active metals, but under calcination or more harsh reaction conditions, the structure is not stable. For example, during high-temperature calcination or high-temperature reaction of core-shell catalysts, the metal particle size grows by more than 5 times, and the two-dimensional material on the surface of the "armor" catalyst cannot exist stably in the high-temperature process. Therefore, the development of a highly dispersed catalyst encapsulated in situ under a reaction state is extremely important for improving the anti-sintering performance and activity of the catalyst.

[0004] On the other hand, although ruthenium and platinum metals have good catalytic decomposition activity for hydrazines and green propellants, they are not easy to disperse evenly and are prone to sintering at high temperatures, which causes their activity to drop rapidly, thus limiting their application in the field of catalytic decomposition of propellants. In-situ encapsulated highly dispersed catalysts can effectively disperse ruthenium and platinum metals, effectively reduce their grain size, improve their activity, and are not easy to sinter at high temperatures. In-situ encapsulated catalysts can realize the application of Ru and Pt in the catalytic field of hydrazines and green propellants, and are expected to replace iridium catalysts. Summary of the invention

[0005] The purpose of the present invention is to provide an in-situ encapsulated catalyst and its application, which realizes in-situ encapsulation of metal nanoparticles in a high-temperature reducing reaction atmosphere, thereby solving the problems of active metal sintering, carbon deposition and volatilization. The catalyst can achieve nearly 100% methane and carbon dioxide conversion rate and syngas selectivity in the methane chemical chain reforming reaction. In addition, the catalyst can also be used for the production of ultrapure hydrogen by solar thermal chemical water splitting and the catalytic decomposition of hydrazine and green propellants.

[0006] To achieve the above purpose, the technical solution of the present invention is as follows:

[0007] The present invention provides an in-situ encapsulated catalyst, which is composed of CeO 2The carrier and the metal nanoparticles loaded on the surface of the carrier are composed of one or more of Ni, Co, Ru and Pt, the particle size of the non-noble metal nanoparticles is 6-20nm (preferably 6-8nm), the particle size of the noble metal nanoparticles is 0.6-2nm, and the loading amount is 0.05-5% of the catalyst mass. 2 The carrier is prepared by co-precipitation method and has a particle size of 15-80 nm (preferably 15-40 nm).

[0008] The specific operation steps are as follows: dissolve a certain amount of active metal precursor in a solvent, stir until completely dissolved, add a stabilizer, heat to 100-180°C (preferably 120-160°C) under stirring, add a reducing agent at this temperature, stir for 2-4h (preferably 2-3h), and cool to room temperature to obtain a stable colloid. Disperse a certain amount of colloid in a solvent, stir evenly, and add a corresponding mass of CeO 2 The carrier is stirred for 18-24h (preferably 18-22h), filtered, washed 5 times, dried at 60-120°C (preferably 80-120°C) for 8-12h (preferably 10-12h), and calcined at 500-900°C (preferably 500-700°C) for 4-8h (preferably 4-6h) in air or inert atmosphere to obtain the catalyst M / CeO 2 . Among the active metal precursors, the nickel active precursor is one or more of nickel chloride, nickel nitrate, nickel formate, nickel acetate or nickel acetylacetonate; the cobalt active metal precursor is one or more of cobalt chloride, cobalt nitrate, cobalt acetate or cobalt acetylacetonate; the platinum active precursor is one or more of chloroplatinic acid, platinum chloride or platinum nitrate; the ruthenium active precursor is ruthenium trichloride, and the active metal loading is 0.05-5% of the catalyst mass. The stabilizer is one or more of polyvinyl pyrrolidone, tri-n-octylphosphine or oleylamine. The reducing agent is NaBH 4 or N 2 H 4 ·H 2 O, the solvent is one or more of water, oleic acid or ethylene glycol. The mass ratio of the stabilizer to the Ni precursor is 1-10 (preferably 5-10), the molar ratio of the reducing agent to the Ni precursor is 1-10 (preferably 5-10), the concentration of the metal particles is 0.1-5 mg / mL (preferably 0.1-2 mg / mL), and the CeO in the solution is 0.1-10. 2 The concentration of the carrier is 5-100 mg / mL (preferably 5-50 mg / mL). 2 The carrier is prepared by a co-precipitation method, the calcination temperature is 500-900° C. (preferably 500-700° C.), the calcination time is 4-8 hours (preferably 4-6 hours), and the particle size is 15-80 nm (preferably 15-40 nm).

[0009] The catalyst is used for chemical chain reforming of methane into synthesis gas, and its metal mass loading is preferably 0.1%-1%. The reaction raw materials are methane and carbon dioxide, respectively. The reaction is carried out in a circulating feeding manner. The prepared catalyst is loaded into a fixed bed reactor, and efficient conversion of methane and carbon dioxide is achieved by adjusting the raw gas volume concentration, space velocity, and reaction time. The product composition is analyzed by online mass spectrometry.

[0010] The catalyst is used in thermochemical cracking hydrogen production (preferably solar thermochemical cracking hydrogen production), and its metal mass loading is preferably 0.1%-1%. The reaction raw materials are water and methane, respectively. The reaction is carried out in a circulating feeding manner. The prepared catalyst is loaded into a fixed bed reactor, and efficient conversion of water and methane is achieved by adjusting the raw gas volume concentration, space velocity, and reaction time. The product composition is analyzed by online mass spectrometry.

[0011] The catalyst is used in the catalytic decomposition of hydrazines and green propellants, and its metal mass loading is preferably 3%-5%. The prepared ruthenium-based and platinum-based catalysts are loaded into a catalytic bed of a propellant engine, and the propellant is supplied by gas squeezing and solenoid valve control. The propellant is catalytically decomposed at room temperature to produce high-temperature and high-pressure combustion gas. The evaluation of the catalyst thermal test performance test is achieved by measuring the engine catalytic bed temperature T, the combustion chamber pressure Pc, and the time t80 from the solenoid valve being energized to the thrust (or the combustion chamber pressure) rising to 80% of the full-course average value.

[0012] Compared with the prior art, the present invention has the following advantages:

[0013] 1. Provides a universal method and strategy for in-situ encapsulation of catalysts. 2 , in the high-temperature reducing atmosphere reaction process, the metal nanoparticles are encapsulated in situ. (The in-situ encapsulated catalyst refers to the surface CeO 2 After being reduced, CeO 2 It can wrap metal nanoparticles to form metal nanoparticles covered by CeO 2 Package structure)

[0014] 2. The catalyst prepared by this method is evenly dispersed and not easy to sinter during the reaction. After 10 hours of high-temperature reaction, its particle size remains almost unchanged.

[0015] 3. The catalyst prepared by this method has an in-situ encapsulation structure formed under the reaction atmosphere, which has higher activity and greater stability for the reaction.

[0016] 4. The in-situ encapsulated catalyst of the present invention can be stably encapsulated in reducing and weakly oxidizing atmospheres, has excellent activity in the methane chemical chain reforming reaction, and promotes its easy formation of CH x , but not easily cracked directly to carbon, the production of 100% ultrapure hydrogen can be achieved in a two-step solar thermochemical water splitting reaction, with very high environmental and economic benefits.

[0017] 5. The in-situ encapsulated catalyst of the present invention can effectively disperse Ru and Pt, effectively reduce their grain size, improve activity, and is not easy to sinter at high temperature. It can realize the application of Ru and Pt in the catalytic field of hydrazine and green propellant, and is expected to replace iridium catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The catalyst of Example 3 of the present invention is used in the cyclic stability test of methane chemical loop reforming. In the figure, the horizontal axis is the number of cycles in the cyclic stability test, the vertical axis on the left is the conversion rate of the reactant methane, the selectivity of the target product carbon monoxide, hydrogen and the by-product carbon dioxide in each cycle, and the vertical axis on the right is the accumulated H in the partial oxidation process of methane in each cycle. 2 / CO ratio and synthesis gas (CO+H 2 ) yield.

[0019] Figure 2 Stability test of the catalyst carbon dioxide conversion step in Example 3 of the present invention, the horizontal axis in the figure is the cycle number of the cyclic stability test, the left vertical axis is the conversion rate of carbon dioxide, and the right vertical axis is the cumulative yield of carbon monoxide.

[0020] Figure 3 The curves on each label correspond to the Raman spectra of the catalysts in Examples 2-4 and Comparative Example 3 after methane pretreatment (where 0.1Ni / CeO 2 Corresponding to the catalyst in Example 2, 1Ni / CeO 2 Corresponding to the catalyst in Example 3, 5Ni / CeO 2 Corresponding to the catalyst in Example 4, 5Ni / CeO 2 -jz corresponds to the catalyst in Example 3), the horizontal axis is the Raman shift, and the vertical axis is the intensity. -1 and 1590cm -1 The peak at the position is the peak of graphite carbon. It can be seen that the 0.1wt.%Ni, 1wt.%Ni and 5wt.%Ni catalysts prepared by the present invention do not generate carbon deposits, which is consistent with Figure 1 The reaction performance results of the catalyst in Example 2 are consistent, but the 5wt.% Ni catalyst prepared by the impregnation method has a large amount of carbon deposits.

[0021] Figure 4 The curves on each label are the XRD patterns of the catalysts in Inventive Examples 2-4 and Comparative Examples 1 and 3 (where CeO 2 Corresponding to the catalyst in Example 1, 0.1Ni / CeO 2 Corresponding to the catalyst in Example 2, 1Ni / CeO 2 Corresponding to the catalyst in Example 3, 5Ni / CeO 2 Corresponding to the catalyst in Example 4, 5Ni / CeO 2 -jz corresponds to the catalyst in Example 3), the horizontal axis is the diffraction angle, and the vertical axis is the diffraction intensity at the corresponding diffraction angle. It can be seen that the catalysts prepared by the method of the present invention with a mass loading of 0.1%, 1%, and 5% have only CeO 2 There is no diffraction peak of NiO, which shows that the preparation method of the present invention can obtain highly dispersed Ni species, while the 5wt.% Ni-jz catalyst prepared by the impregnation method has a diffraction peak of NiO, indicating that its dispersion is poor.

[0022] Figure 5 The STEM image of the Ni nanoparticles prepared in the first step of Example 2 of the present invention shows that the Ni nanoparticle colloid is evenly dispersed, indicating that the Ni nanoparticle colloid obtained by the preparation method of the present invention has a uniform size of 6-8 nm.

[0023] Figure 6 The element distribution diagram of the catalysts in Examples 2-4 of the present invention and Comparative Example 3 (wherein a corresponds to the catalyst in Example 2, b corresponds to the catalyst in Example 3, c corresponds to the catalyst in Example 4, and d corresponds to the catalyst in Comparative Example 3). It can be seen from the figure that the catalysts in Examples 2-4 still maintain a highly dispersed state after calcination without obvious aggregation, while the catalyst in Comparative Example 3 is highly aggregated, and the particle size is roughly above 50 nm according to the scale.

[0024] Figure 7 HRTEM images of the catalyst after reduction and circulation in Example 3 of the present invention (where a corresponds to the catalyst after reduction in Example 3, and b corresponds to the catalyst after reaction in Example 3), the numbers represent the lattice fringe spacing, which are CeO 2 From the 111 faces of (0.33, 0.31 nm) and the 111 faces of Ni (0.20 nm), it can be seen that the catalyst particle sizes after the methane partial oxidation step (a) and the carbon dioxide cracking step (b) are relatively small, and the coating structure is maintained, with very high anti-sintering ability.

[0025] Figure 8HRTEM and Mapping images of the catalyst after reduction and circulation in Comparative Example 3 of the present invention (where a corresponds to the HTRTEM image of the catalyst after reduction in Comparative Example 3, b corresponds to the HTRTEM image of the catalyst after reaction in Comparative Example 3, and c corresponds to the Mapping image of the catalyst after reaction in Comparative Example 3), the numbers represent the lattice fringe spacing, which are CeO 2 The 111 faces of (0.32, 0.31 nm) and the 111 faces of Ni (0.20 nm) show that the catalyst particles after the methane partial oxidation step (a) and the carbon dioxide cracking step (b) are larger, without obvious coating structure, and are obviously sintered and grown compared with the fresh samples.

[0026] Fig. 9 CO in-situ diffuse reflectance infrared spectra (CO-DRIFTS) of fresh and recycled catalysts in Examples 3-4 of the present invention and Comparative Example 3 (where a corresponds to the catalyst in Example 3, b corresponds to the catalyst after reaction in Example 3, c corresponds to the catalyst in Example 4, d corresponds to the catalyst after reaction in Example 4, e corresponds to the catalyst in Comparative Example 3, and f corresponds to the catalyst after reaction in Comparative Example 3). 2176 cm -1 and 2112cm -1 The peak is the peak of gas phase CO, marked with 2066cm -1 、2124cm -1 and 2078cm -1 The peak is the linear adsorption peak of CO on Ni, marked with 1927 cm -1 The peak is the bridge adsorption peak of CO on Ni. The larger the peak wave number, the higher the Ni dispersion. It can be seen that the dispersion of 1wt.% Ni and 5wt.% Ni is significantly higher than that of 5wt.% Ni-jz, which is consistent with Figure 6-8 The results in the previous study are consistent. The fresh 1wt.%Ni and 5wt.%Ni catalysts have obvious CO adsorption peaks on Ni, but after cycling, the adsorption peaks disappear, which once again proves that Ni is absorbed by CeO 2 coating, while for the catalyst with 5wt.% Ni-jz, its adsorption peak still exists, proving that it is not coated after cycling, and the high wavenumber peak disappears and the intensity weakens, indicating that part of the active metal is sintered and grown.

[0027] Fig.10 The stability test of solar thermal chemical water splitting by the catalyst of the present invention, the horizontal axis is the number of cycles, the vertical axis is H 2 The peak generation rate and cumulative generation in a single cycle.

[0028] Fig.11Ignition test data of DT-3, ADN and HAN based propellant engines of the Ru catalyst prepared in Example 25 of the present invention. a is the ignition test data of DT-3 propellant engine, b is the ignition test data of ADN based propellant engine, and c is the ignition test data of HAN based propellant engine.

[0029] Fig.12 XRD patterns of the catalysts in Examples 25 and 26 of the present invention (5Ru / CeO 2 Corresponding to the catalyst in Example 25, 5Pt / CeO 2 The corresponding catalyst in Example 26), the horizontal axis is the diffraction angle, and the vertical axis is the diffraction intensity at the corresponding diffraction angle. It can be seen that only CeO 2 There are no diffraction peaks of Ru and Pt, which shows that the preparation method of the present invention can obtain highly dispersed Ru and Pt species.

[0030] Fig.13 The STEM image of the Ru nanoparticles prepared in the first step in Example 25 of the present invention shows that the Ru nanoparticle colloid is evenly dispersed, indicating that the Ru nanoparticle colloid obtained by the preparation method of the present invention has a uniform size of 0.6-1.5nm.

[0031] Fig.14 The STEM images of the catalysts in Examples 25 and 26 of the present invention (where a corresponds to the catalyst in Example 25 and b corresponds to the catalyst in Example 26) show that after loading and calcination in an inert atmosphere, the Ru and Pt nanoparticles are still evenly dispersed, with a size of 0.8-1.6 nm.

[0032] Fig.15 XRD patterns of the catalysts in Examples 25 and 26 of the present invention after reaction (5Ru / CeO 2 Corresponding to the catalyst in Example 25, 5Pt / CeO 2 The corresponding catalyst in Example 26), the horizontal axis is the diffraction angle, and the vertical axis is the diffraction intensity at the corresponding diffraction angle. It can be seen that only CeO 2 There are no diffraction peaks of Ru and Pt, which indicates that the catalyst prepared by the preparation method of the present invention has very good anti-sintering ability during the reaction process.

[0033] Fig.16 The STEM images of the catalysts in Examples 25 and 26 of the present invention after reaction (where a corresponds to the catalyst in Example 25 after reaction, and b corresponds to the catalyst in Example 26 after reaction) show that the Ru nanoparticles are evenly dispersed, indicating that the catalyst obtained by the preparation method of the present invention has very good anti-sintering ability. DETAILED DESCRIPTION

[0034] The following examples use CeO 2 The carrier is prepared by coprecipitation method, and the specific process is as follows: 16g of cerium nitrate hexahydrate is weighed and dissolved in 200mL of deionized water, and after being fully stirred, 25wt.% ammonia water is added to pH=9 under stirring at 80°C, stirred for 3h, aged for 1h, filtered and washed 3 times, and then placed in a 120°C oven for drying for 12h. After grinding, the temperature is raised to 500°C at a rate of 5°C / min in an air atmosphere, and calcined at this temperature for 4h, and the particle size is 15-20nm.

[0035] The following examples will help to understand the present invention, but the protection scope of the present invention is not limited to these examples.

[0036] Examples 1-4

[0037] Take 0.24g of nickel chloride hexahydrate and place it in a flask. Add 100mL of ethylene glycol and stir magnetically. Then add 1.2g of polyvinyl pyrrolidone and heat to 140℃ while stirring. At the same time, condense and reflux. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2 h, stop heating, cool to room temperature, and obtain stable metal nanoparticle colloids, which are stored for later use. Take 0.85 mL, 1.69 mL, 16.87 mL, and 84.35 mL of Ni nanoparticle colloids in a beaker, add ethylene glycol to a total volume of 100 mL, stir magnetically, and then add 1 g, 1 g, 0.99 g, and 0.95 g of CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain Ni / CeO with Ni mass loadings of 0.05%, 0.1%, 1%, and 5%, respectively. 2 catalyst.

[0038] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 / He feed operation, the temperature is kept constant throughout the reaction process, the reaction tail gas is quantitatively detected by online mass spectrometry, and the cycle results are shown in Figure 1 and Figure 2 The cumulative product distribution is shown in Table 1. It can be seen that the Ni / CeO 2The catalyst has excellent resistance to carbon deposition and sintering, and because its in-situ encapsulation structure has a large number of defect sites, 100% methane and carbon dioxide conversion can be achieved at a mass loading of 0.1%.

[0039] Comparative Example 1

[0040] Take 0.2g CeO 2 The catalyst was added to the fixed bed reactor and heated to 900°C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 1.

[0041] Comparative Examples 2-3

[0042] Take 1g and 0.95g CeO respectively 2 The carrier was added to the nickel nitrate aqueous solution to make the Ni mass loading amount 0.1% and 5%, respectively. After stirring evenly, 25wt.% ammonia water was added dropwise, and the pH was adjusted to 9. After stirring for 3h, the catalyst was filtered and washed 3 times, and then placed in a drying oven and dried at 120℃ for 12h. The dried catalyst was calcined at 500℃ in air atmosphere for 4h to obtain Ni / CeO with mass loading of 0.1% and 5%, respectively. 2 Catalyst (0.1Ni / CeO 2 -jz and 5Ni / CeO 2 -jz). 0.2 g of the catalyst was added to a fixed bed reactor, and the temperature was raised to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 1.

[0043] Table 1 Different loading amounts of Ni / CeO 2 Product distribution of catalyst

[0044]

[0045] From the results of Examples 2-4 and Comparative Example 1 above, it can be seen that the catalyst prepared by the present invention achieves nearly 100% methane and carbon dioxide conversion rate and carbon monoxide selectivity in the methane chemical chain conversion process. Figure 5 , 6 It can be seen from ac that the particle sizes of Ni nanoparticle colloid and Ni nanoparticles in Examples 2-4 are all 6-8nm. Figure 7 It can be seen that the catalyst of Example 3 can form an in-situ encapsulated coating structure during the reaction process, effectively activate methane and carbon dioxide, and can well avoid sintering and carbon deposition of active metals. The particle size of Ni nanoparticles is kept within 10nm, which promotes the improvement of stability. According to the requirements of atomic economy, the loading amount of active metals can be preferably 0.1-1%. From the results of the above comparative examples 2-3, it can be seen that the catalyst prepared by the impregnation method is difficult to achieve complete conversion of methane and carbon dioxide at a lower loading. When the mass loading reaches 5%, although the methane conversion rate is greatly improved, it is very easy to deposit carbon during the reaction process, the selectivity of synthesis gas is greatly reduced, and H 2 The ratio of / CO is not suitable for production in downstream industrial processes.

[0046] Embodiment 5-6

[0047] Take 0.05g, 0.41g, and 0.8g of nickel chloride hexahydrate respectively and place them in a flask, add 100mL of ethylene glycol, stir magnetically, then add 0.2g, 2g, and 4g of polyvinyl pyrrolidone respectively, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.04g, 0.32g, and 0.64g of NaBH 4 , stirred vigorously for 2 h, stopped heating, cooled to room temperature, and obtained metal nanoparticles with concentrations of 0.12 mg / mL, 1.01 mg / mL, and 1.98 mg / mL, respectively, which were stored for later use. 8.4 mL, 1 mL, and 0.51 mL of Ni nanoparticle colloid were placed in beakers, ethylene glycol was added to the total volume of each liquid to 100 mL, magnetic stirring was performed to evenly mix, and then 1 g CeO was added to each 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -0.1, 0.1Ni / CeO 2 -1, 0.1Ni / CeO 2 -2.

[0048] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 2.

[0049] Comparative Examples 4-5

[0050] Take 1.2g and 2.0g of nickel chloride hexahydrate respectively and place them in a flask, add 100mL of ethylene glycol, stir magnetically, then add 6g and 10g of polyvinyl pyrrolidone respectively, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.96g and 1.59g of NaBH 4 , stirred vigorously for 2 h, stopped heating, cooled to room temperature, and obtained metal nanoparticles with concentrations of 2.96 mg / mL and 4.94 mg / mL, respectively, which were stored for later use. 0.34 mL and 0.21 mL of Ni nanoparticle colloid were placed in a beaker, ethylene glycol was added to the total volume of the liquid to 100 mL, magnetic stirring was performed, and then 1 g CeO was added to each 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -3 and 0.1Ni / CeO 2 -5.

[0051] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 2.

[0052] Table 2 Catalytic results of catalysts with different precursor concentrations

[0053]

[0054] From the results of Examples 2, 5-7 and Comparative Examples 4 and 5, it can be seen that the Ni / CeO 2 The catalyst has a conversion rate and selectivity of nearly 100% in methane chemical chain conversion. The particle size of its metal nanoparticles is 6-8nm. After 20h of reaction time, the particle size of Ni nanoparticles remains within 10nm and is supported by CeO 2 Very good coating can effectively avoid the formation of carbon deposits. From the results of Comparative Examples 4 and 5, it can be seen that when the concentration of Ni nanoparticle precursor is relatively high, about 60%-80% of the Ni nanoparticles have a particle size of 6-8nm, and the remaining Ni nanoparticles have a particle size of 15-20nm. The particle size is large, and it is difficult to achieve an in-situ coating structure, and the number of active sites is relatively reduced. However, it can be seen from Tables 2 and 1 that compared with the catalyst with the same loading prepared by the impregnation method, it still has more than twice the activity, proving that the catalyst prepared by this method has a very large advantage over the traditional impregnation method. However, from the perspective of atom economy and conversion rate, the concentration of active metal precursors may preferably be 0.1-2mg / mL.

[0055] Examples 8-10

[0056] Take 0.24g of nickel chloride hexahydrate and place it in three flasks, add 100mL of ethylene glycol to each flask, stir magnetically, then add 1.68g, 2.16g and 2.4g of polyvinyl pyrrolidone respectively, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, and obtain stable metal nanoparticle colloid, which is stored for future use. Take 1.69mL Ni nanoparticle colloid and place it in a beaker, add ethylene glycol to the total volume of the liquid to 100mL, stir evenly with a magnetic stirrer, and then add 1g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -P-7, 0.1Ni / CeO 2 -P-9 and 0.1Ni / CeO 2 -P-10.

[0057] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 3.

[0058] Comparative Examples 6-8

[0059] Take 0.24g of nickel chloride hexahydrate and place it in three flasks, add 100mL of ethylene glycol to each flask, stir evenly with magnetic stirring, then add 0.24g, 0.48g and 0.96g of polyvinyl pyrrolidone respectively, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, and store for later use. Take 1.69mL of Ni nanoparticle colloid and place it in a beaker, add ethylene glycol to the total volume of the liquid to 100mL, stir evenly with a magnetic stirrer, and then add 1g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -P-1, 0.1Ni / CeO 2 -P-2 and 0.1Ni / CeO 2 -P-4.

[0060] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 3.

[0061] Table 3 Catalytic results of catalysts with different PVP to Ni precursor mass ratios

[0062]

[0063] From the results of Examples 2 and 8-10 above, it can be seen that the catalyst with a higher PVP / Ni precursor mass ratio (>4) has a stronger protective effect, making the size of the Ni nanoparticles smaller and uniform, and the particle size of the metal nanoparticles is 6-8nm, which is conducive to realizing the in-situ coating structure, and has a good catalytic result in the chemical chain conversion of methane. After 20h of reaction time, the particle size of the Ni nanoparticles remains within 10nm. From the results of Comparative Examples 6-8 and Comparative Example 2, it can be seen that when the protective agent is less, the active metal is easy to aggregate and grow during the preparation and calcination process, and about 20%-30% of the Ni nanoparticles are 15-20nm. It is difficult to form a coating structure during the reaction process, the number of active sites is small and it is easy to deposit carbon, and it is difficult to achieve efficient conversion of methane, but it is still more than twice as active as the catalyst with the same loading prepared by the direct impregnation method, proving that the catalyst prepared by this method has a very large advantage over the traditional impregnation method. However, from the perspectives of atom economy and conversion rate, the mass ratio of the stabilizer to the active metal precursor may preferably be 5-10.

[0064] Examples 11-12

[0065] Take 0.24g of nickel chloride hexahydrate and place it in two flasks, add 100mL of ethylene glycol to each flask, stir magnetically, then add 1.2g of polyvinyl pyrrolidone, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.31g and 0.38g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, obtain stable metal nanoparticle colloid, and store for later use. Take 1.69mL Ni nanoparticle colloid and place it in a beaker, add ethylene glycol to the total volume of the liquid to 100mL, stir evenly with a magnetic stirrer, and then add 1g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -R-8 and 0.1Ni / CeO 2 -R-10.

[0066] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 4.

[0067] Comparative Examples 9-10

[0068] Take 0.24g of nickel chloride hexahydrate and place it in two flasks, add 100mL of ethylene glycol to each flask, stir magnetically, then add 1.2g of polyvinyl pyrrolidone, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.04g and 0.12g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, and store for later use. Take 1.69mL of Ni nanoparticle colloid and place it in a beaker, add ethylene glycol to the total volume of the liquid to 100mL, stir evenly with a magnetic stirrer, and then add 1g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -R-1 and 0.1Ni / CeO 2 -R-3.

[0069] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 4.

[0070] Table 4 Catalytic results of catalysts with different molar ratios of reducing agent to Ni precursor

[0071]

[0072]

[0073] From the results of Examples 2, 11, and 12 above, it can be seen that higher NaBH 4 / Ni precursor molar ratio (> 4) catalyst, can effectively reduce Ni precursor and generate nanoparticles with uniform particle size, the particle size of its metal nanoparticles is 6-8nm, can achieve nearly 100% methane, carbon dioxide conversion rate and synthesis gas selectivity, after 20h reaction time, Ni nanoparticle particle size remains within 10nm. From comparative examples 9-10 and comparative example 2 results, it can be known that when the reducing agent is less, it is easy to react with the solvent itself, resulting in a part of Ni cannot be reduced, existing in the form of metal ions, similar to the direct impregnation method, this part is relatively less active, and is easy to grow up to 20nm with other Ni nanoparticles, active sites are reduced and difficult to achieve coating, but its overall activity is compared with the same loading catalyst prepared by the direct impregnation method, still has more than 2 times its activity, proving that the catalyst prepared by this method has a very large advantage compared with the traditional impregnation method. But from the perspectives of atom economy and conversion rate, the molar ratio of reducing agent to active metal precursor can be preferably 5-10.

[0074] Examples 13-15

[0075] Take 0.24g of nickel chloride hexahydrate and place it in a flask. Add 100mL of ethylene glycol and stir magnetically. Then add 1.2g of polyvinyl pyrrolidone and heat to 140℃ while stirring. At the same time, condense and reflux. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, obtain stable metal nanoparticle colloid, and store for later use. Take 1.69mL Ni nanoparticle colloid and place it in 3 beakers, add ethylene glycol to the total volume of each liquid to 20mL, 50mL, and 200mL respectively, stir evenly with magnetic stirring, and then add 1g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain catalysts, which were respectively denoted as 0.1Ni / CeO 2 -20, 0.1Ni / CeO 2 -50, 0.1Ni / CeO 2 -200.

[0076] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO2 / He feed operation, the temperature was kept constant throughout the reaction process, the reaction tail gas was quantitatively detected by online mass spectrometry, and the cumulative product distribution is shown in Table 5.

[0077] Comparative Examples 11-12

[0078] Take 0.24g of nickel chloride hexahydrate and place it in a flask. Add 100mL of ethylene glycol and stir magnetically. Then add 1.2g of polyvinyl pyrrolidone and heat to 140℃ while stirring. At the same time, condense and reflux. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2 h, stop heating, cool to room temperature, and obtain stable metal nanoparticle colloid, which is stored for future use. Take 1.69 mL of Ni nanoparticle colloid and place it in two beakers, add ethylene glycol to the total volume of each liquid to 10 mL and 15 mL respectively, stir evenly with a magnetic stirrer, and then add 1 g of CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain a Ni / CeO catalyst with a mass loading of 0.1%. 2 catalyst, respectively denoted as 0.1Ni / CeO 2 -10, 0.1Ni / CeO 2 -15.

[0079] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 The reaction was carried out by feeding / He into the reaction mixture. The temperature was kept constant during the whole reaction process. The reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 5.

[0080] Table 5 Different CeO in solution 2 Concentration of Ni / CeO 2 Product distribution of catalyst

[0081]

[0082] As can be seen from the above examples 13-15, the catalyst prepared by the present invention achieves nearly 100% methane and carbon dioxide conversion rate and carbon monoxide selectivity in the methane chemical chain conversion process. The particle size of the Ni nanoparticles in Examples 13-15 is 6-8nm. During the reaction process, an in-situ encapsulated coating structure can be formed to effectively activate methane and carbon dioxide, and at the same time, the sintering and carbon deposition of active metals can be well avoided. The particle size of the Ni nanoparticles is kept within 10nm, which promotes the improvement of stability. As can be seen from the results of Comparative Examples 11-12 and Comparative Example 2, when CeO 2 When the concentration is too high, the methane conversion rate is reduced, mainly because some of the Ni nanoparticles are unevenly distributed on the carrier during the stirring process. After calcination, the particle size is about 15-20nm, but the main part is between 6-8nm, which is more than twice the activity of the impregnation catalyst with the same loading, proving that the catalyst prepared by this method has a great advantage over the traditional impregnation method. However, from the perspective of atom economy and conversion rate, CeO 2 The concentration in solution may preferably be 5-50 mg / mL.

[0083] Examples 16-19

[0084] Take 0.24g of cobalt chloride hexahydrate and place it in a flask, add 100mL of ethylene glycol, stir magnetically, then add 1.2g of polyvinyl pyrrolidone, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2 h, stop heating, cool to room temperature, and store for later use. Take 1.69 mL, 8.44 mL, 16.82 mL, and 84.1 mL of Co nanoparticle colloid respectively and place them in a beaker, add ethylene glycol until the total volume of each liquid is 100 mL, stir evenly with a magnetic stirrer, and then add 1 g, 1 g, 0.99 g, and 0.95 g of CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain Co / CeO with Co mass loadings of 0.1%, 0.5%, 1%, and 5%, respectively. 2 catalyst.

[0085] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5vol% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH4 / He, CO 2 / He feed operation, the temperature was kept constant throughout the reaction process, the reaction tail gas was quantitatively detected by online mass spectrometry, and the cumulative product distribution is shown in Table 6.

[0086] Comparative Examples 13-14

[0087] Take 1g and 0.95g CeO respectively 2 The carrier was added to the cobalt nitrate aqueous solution to make the mass loading of Co 0.1% and 5%, respectively. After stirring evenly, 25wt.% ammonia water was added dropwise, and the pH was adjusted to 9. After stirring for 3 hours, the catalyst was filtered and washed three times, and then placed in a drying oven and dried at 120°C for 12 hours. The dried catalyst was calcined at 500°C in an air atmosphere for 4 hours to obtain Co / CeO with mass loading of 0.1% and 5%, respectively. 2 Catalyst (0.1Co / CeO 2 -jz and 5Co / CeO 2 -jz).

[0088] 0.2 g of catalyst was added to a fixed bed reactor and heated to 900 °C under an inert atmosphere of He. After the temperature stabilized, 5 vol% CH 4 / He, flow rate 15mL / min, after 8min, switch to He gas purge for 5min, pass 5% CO 2 / He, flow rate 15mL / min, 8min later switched to He purge for 5min, repeating the above CH 4 / He, CO 2 / He feed operation, the temperature was kept constant throughout the reaction process, the reaction tail gas was quantitatively detected by online mass spectrometry, and the cumulative product distribution is shown in Table 6.

[0089] Table 6 Different loading amounts of Co / CeO 2 Product distribution of catalyst

[0090]

[0091] From the results of Examples 16-19 and Comparative Examples 13-14 above, it can be seen that the Co / CeO 2 Catalysts have Ni / CeO in methane chemical looping 2 Almost the same activity, the particle size of Co nanoparticles is 6-8nm, and an in-situ encapsulation structure is formed during the reaction, and the high-defect CeO coated on the surface of Co nanoparticles 2It effectively activates methane and carbon dioxide, and avoids carbon deposition and sintering of active metals. The particle size of the Co nanoparticles after the reaction is below 10nm, which has very high stability. The Co-based catalyst prepared by the impregnation method has very low activity at low loadings, and can achieve complete conversion at high loadings. However, the particle size of the metal Co nanoparticles is large, above 50nm, which makes it easy to directly crack methane into carbon, resulting in a lower CO generation rate than H 2 The generation rate is not conducive to the subsequent process, and the particle size of the Co nanoparticles after the reaction reaches more than 100nm.

[0092] Examples 21-24

[0093] Take 0.24g of nickel chloride hexahydrate and place it in a flask. Add 100mL of ethylene glycol and stir magnetically. Then add 1.2g of polyvinyl pyrrolidone and heat to 140℃ while stirring. At the same time, condense and reflux. At 140℃, add 0.2g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, and obtain stable Ni nanoparticle colloid, which is stored for later use. Take 1.69mL, 8.44mL, 16.87mL, and 84.35mL of Ni nanoparticle colloid respectively and place them in a beaker, add ethylene glycol to make the total volume of each liquid 100mL, stir evenly with magnetic force, and then add 1g, 1g, 0.99g, and 0.95g CeO 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an air atmosphere to obtain Ni / CeO with mass loadings of 0.1%, 0.5%, 1%, and 5%, respectively. 2 catalyst.

[0094] The fixed bed was heated by an infrared gold image furnace to simulate the solar thermal collection system for solar thermal chemical water splitting reaction. 0.2 g of catalyst was added to the fixed bed reactor and heated to 900 °C under an inert atmosphere of Ar at a heating rate of 100 °C / min. After the temperature stabilized, 1 vol% CH 4 / Ar was used for reduction at a flow rate of 100 mL / min. After 6 min, the gas was switched to Ar for 5 min and 4.2 vol% H 2 O / Ar, flow rate 700mL / min, after 6min, switch to Ar purge for 5min, repeat the above CH 4 / Ar、H 2 O / Ar feed operation, the temperature is kept constant throughout the reaction process, the reaction tail gas is quantitatively detected by online mass spectrometry, and the cycle results are shown in Fig.10 , the cumulative product distribution is shown in Table 7.

[0095] Comparative Example 15

[0096] Take 0.95g CeO 2 The carrier was added to the nickel nitrate aqueous solution to make the Ni mass loading amount 5%, and then 25wt.% ammonia water was added dropwise after stirring evenly, and the pH was adjusted to 9, and stirred for 3h. After filtration and washing, it was placed in a drying oven and dried at 120℃ for 12h. The dried catalyst was calcined at 500℃ in air atmosphere for 4h to obtain Ni / CeO with a mass loading of 5%. 2 Catalyst (5Ni / CeO 2 -jz). An infrared gold image furnace was used to simulate the solar thermal collection system to heat the fixed bed for solar thermal chemical water splitting reaction. 0.2 g of catalyst was added to the fixed bed reactor and heated to 900 °C under an inert atmosphere of Ar at a heating rate of 100 °C / min. After the temperature stabilized, 1 vol% CH 4 / Ar was used for reduction at a flow rate of 100 mL / min. After 6 min, the gas was switched to Ar for 5 min and 4.2 vol% H 2 O / Ar, flow rate 700mL / min, after 6min, switch to Ar purge for 5min, repeat the above CH 4 / Ar、H 2 O / Ar feed operation, the temperature was kept constant throughout the reaction process, and the reaction tail gas was quantitatively detected by online mass spectrometry. The cumulative product distribution is shown in Table 7

[0097] Table 7 Different loading amounts of Ni / CeO 2 Product distribution of solar thermochemical water splitting over catalysts

[0098]

[0099]

[0100] According to the above examples 21-24, the Ni / CeO 2 The catalyst has a H rate of about 122 mL / min / g in solar thermochemical water splitting to produce hydrogen. 2 The peak rate and total hydrogen production of about 37 mL / g per cycle, the methane partial oxidation process can form an in-situ encapsulation structure, the particle size of the Ni nanoparticles is less than 10 nm, and the high-defect CeO coated on the surface of the Ni nanoparticles 2 Effective activation of methane to CH x , will not directly split to carbon, so the water splitting process H 2 The purity is 100%, which greatly improves the economic and environmental benefits. 2During the partial oxidation of methane, Ni nanoparticles tend to grow to more than 100 nm and form carbon deposits. 2 O reacts with carbon to generate CO, which reduces the purity of hydrogen and is not conducive to production.

[0101] Embodiment 25

[0102] Take 0.12g of ruthenium trichloride and put it in a flask. Add 100mL of ethylene glycol and stir magnetically. Then add 0.6g of polyvinyl pyrrolidone and heat to 140℃ while stirring. At the same time, condense and reflux. At 140℃, add 0.11g of NaBH 4 , stir vigorously for 2h, stop heating, cool to room temperature, and obtain stable metal nanoparticle colloid, which is stored for future use. Take 85.4mL of Ru nanoparticle colloid and place it in a beaker, add ethylene glycol until the total volume of the liquid is 100mL, stir evenly with a magnetic stirrer, and then add 0.95g of CeO prepared by coprecipitation method. 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an argon atmosphere to obtain a Ru / CeO catalyst with a mass loading of 5%. 2 catalyst.

[0103] The prepared high-load ruthenium-based catalyst is loaded into the catalytic bed of the propellant engine, and the propellant is supplied by gas squeezing and solenoid valve control. The propellant is catalytically decomposed at room temperature to produce high-temperature and high-pressure combustion gas. The evaluation of the catalyst hot test performance is achieved by measuring the engine catalytic bed temperature T, the combustion chamber pressure Pc, and the time t80 from the solenoid valve being energized to the thrust (or combustion chamber pressure) rising to 80% of the full-course average value.

[0104] from Fig.11 It can be seen that the prepared Ru-based catalyst has good catalytic decomposition activity and stability of hydrazine and green propellant. Fig.14 and Fig.16 It can be seen that the Ru nanoparticles before and after the reaction are kept below 2 nm, showing very high stability.

[0105] Embodiment 26

[0106] Take 0.12g of chloroplatinic acid hydrate and place it in a flask, add 100mL of ethylene glycol, stir magnetically, then add 0.6g of polyvinyl pyrrolidone, heat to 140℃ while stirring, and reflux at the same time. At 140℃, add 0.06g of NaBH 4, stir vigorously for 2h, stop heating, cool to room temperature, and obtain stable metal nanoparticle colloid, which is stored for future use. Take 87.5mL of Pt nanoparticle colloid and place it in a beaker, add ethylene glycol to a total liquid volume of 100mL, stir evenly with a magnetic stirrer, and then add 0.95g of CeO prepared by coprecipitation method. 2 The carrier was stirred for 18 hours, filtered, washed 5 times, and placed in a drying oven to dry at 120°C for 12 hours. The dried catalyst was calcined at 500°C for 4 hours in an argon atmosphere to obtain a Pt / CeO with a mass loading of 5%. 2 catalyst.

[0107] The prepared high-load platinum-based catalyst is loaded into the catalyst bed of the propellant engine, and the propellant is supplied by gas squeezing and solenoid valve control. The propellant is catalytically decomposed at room temperature to produce high-temperature and high-pressure combustion gas. The evaluation of the catalyst thermal test performance test is achieved by measuring the engine catalyst bed temperature T, the combustion chamber pressure Pc, and the time t80 from the solenoid valve being energized to the thrust (or combustion chamber pressure) rising to 80% of the average value of the entire process. The Pt nanoparticles before and after the reaction are kept below 2nm, with good hydrazine and green propellant catalytic decomposition activity and very high metal nanoparticle stability.

Claims

1. An in-situ encapsulated catalyst, characterized in that: The catalyst is composed of a CeO2 carrier and active metal nanoparticles loaded on the surface of the carrier, wherein the active metal is one or more of Ni, Co, Ru, and Pt, and the active metal loading in the catalyst is 0.05-5% of the catalyst mass; The preparation process of the in-situ encapsulated catalyst is as follows: 1) Dissolve the active metal precursor in the solvent, add the stabilizer, and heat to 100-180 o C, add reducing agent, stir for 2-4 h, and cool to room temperature to obtain a stable colloid; 2) Disperse the colloid in the solvent, stir evenly, add the required mass of CeO2 carrier, stir for 18-24 hours, separate the solid and liquid, wash the solid, and heat for 60-120 o C for 8-12 h, 500-900 °C in air and / or inert atmosphere o C was calcined for 4-8 h to obtain the catalyst M / CeO2; The nickel active precursor in the active metal precursor is one or more of nickel chloride, nickel nitrate, nickel formate, nickel acetate or nickel acetylacetonate; the cobalt active metal precursor is one or more of cobalt chloride, cobalt nitrate, cobalt acetate or cobalt acetylacetonate; the platinum active precursor is one or more of chloroplatinic acid, platinum chloride or platinum nitrate; the ruthenium active precursor is ruthenium trichloride; The stabilizer is one or more of polyvinyl pyrrolidone, tri-n-octylphosphine or oleylamine; The reducing agent is one or both of NaBH4 and N2H4‧H2O; The solvent is one or more of water, oleic acid or ethylene glycol.

2. The in-situ encapsulated catalyst according to claim 1, characterized in that: The preparation process of the in-situ encapsulated catalyst is as follows: 1) Dissolve the active metal precursor in the solvent, add the stabilizer, and heat to 120-160 o C, add reducing agent, stir for 2-3 h, and cool to room temperature to obtain a stable colloid; 2) Disperse the colloid in the solvent, stir evenly, add the required mass of CeO2 carrier, stir for 8-22 hours, separate the solid and liquid, wash the solid, 80-120 o C for 10-12 h, 500-700 °C in nitrogen or one or more inert gases atmosphere o C is calcined for 4-6 h to obtain the catalyst M / CeO2.

3. The in-situ encapsulated catalyst according to claim 1, characterized in that: The mass ratio of the stabilizer to the active metal precursor is 1-10, and the molar ratio of the reductant to the active metal precursor is 1-10; in step 1), the active metal precursor is dissolved in the solvent and the metal nanoparticle concentration is 0.1-5 mg / mL, the particle size of the prepared non-precious metal nanoparticles is 6-20 nm, and the particle size of the precious metal nanoparticles is 0.6-2 nm; in step 2), the concentration of the CeO2 carrier in the solution is 5-100 mg / mL.

4. The in-situ encapsulated catalyst according to claim 3, characterized in that: The mass ratio of the stabilizer to the active metal precursor is 5-10, and the molar ratio of the reductant to the active metal precursor is 5-10; in step 1), the active metal precursor is dissolved in the solvent and its metal nanoparticle concentration is 0.1-2 mg / mL, the particle size of the prepared non-precious metal nanoparticles is 6-8 nm, and the particle size of the precious metal nanoparticles is 0.6-2 nm; in step 2), the concentration of the CeO2 carrier in the solution is 5-50 mg / mL.

5. The in-situ encapsulated catalyst according to claim 1, characterized in that: The CeO2 carrier is prepared by co-precipitation method, using soluble salt as raw material, precipitating in alkaline aqueous solution and then calcining in air, and the calcination temperature is 500-900 o C, calcination time is 4-8 h, and particle size is 15-80 nm.

6. The in-situ encapsulated catalyst according to claim 5, characterized in that: The CeO2 carrier is prepared by coprecipitation method, using soluble salt as raw material, precipitating in alkaline aqueous solution and then calcining in air, and the calcination temperature is 500-700 o C, calcination time is 4-6 h, and particle size is 15-40 nm.

7. The in-situ encapsulated catalyst according to claim 1, characterized in that: In a high-temperature reducing reaction atmosphere, the metal nanoparticles are in-situ encapsulated by the carrier CeO2. After a long period of reaction, they still maintain a highly dispersed state without obvious growth. The particle size of non-precious metal Ni and / or Co nanoparticles remains below 10 nm, and the particle size of precious metal Ru and / or Pt nanoparticles continues to remain below 2 nm.

8. Use of the catalyst according to any one of claims 1 to 7, characterized in that: The catalyst is used in the reaction of methane chemical chain reforming to produce synthesis gas. The reaction raw materials are methane and carbon dioxide, and the reaction is carried out in a cyclic alternating feeding mode. The active metal loading in the catalyst is 0.05-5% of the catalyst mass.

9. The use according to claim 8, characterized in that: The active metal loading in the catalyst is 0.1%-1% of the catalyst mass.

10. Use of the catalyst according to any one of claims 1 to 7, characterized in that: The catalyst is used in the production of hydrogen by thermochemical cracking. The reaction raw materials are water vapor and methane respectively. The reaction is carried out in a cyclic alternating feeding mode. The active metal loading in the catalyst is 0.05-5% of the catalyst mass.

11. The use according to claim 10, characterized in that: In the solar thermal chemical cracking hydrogen production of the catalyst, the reaction raw materials are water vapor and methane respectively, and the reaction is carried out in a cyclic alternating feeding mode. The active metal loading in the catalyst is 0.1%-1% of the catalyst mass.

12. Use of the catalyst according to any one of claims 1 to 7, characterized in that: The catalyst is used for catalytic decomposition of hydrazine propellants, ADN-based or HAN-based green propellants, and the active metal loading in the catalyst is 0.05-5% of the catalyst mass.

13. The use according to claim 12, characterized in that: The active metal loading in the catalyst is 3%-5% of the catalyst mass.

Citation Information

Patent Citations

  • Two-step method solar thermochemical energy storage non-noble metal catalyst, preparation and applications thereof

    CN111215085A